2011
DOI: 10.1016/j.ijrobp.2010.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Epidermal Growth Factor Receptor Assay With Clinical Parameters Improves Risk Classification for Relapse and Survival in Head-and-Neck Squamous Cell Carcinoma

Abstract: PURPOSE Epidermal growth factor receptor (EGFR) overexpression has been consistently found to be an independent predictor of local-regional relapse (LRR) after radiotherapy. We assessed the extent by which it can refine risk classification for overall survival (OS) and LRR in patients with head and neck squamous cell carcinoma (HNSCC). METHODS AND MATERIALS EGFR expression in locally advanced HNSCC was measured by immunohistochemistry (IHC) in a series of patients randomized to receive accelerated or convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…It has long been understood that EGFR overexpression as determined by immunohistochemistry is associated with poor survival in HNSCC patients. [5][6][7][8] Furthermore, recent comprehensive genomic analyses of HNSCCs have confirmed that EGFR is altered by increased copy number and mutations. [9][10][11] Based on these data, EGFR-targeted agents have been developed and cetuximab, a monoclonal antibody directed against EGFR, is currently FDA-approved for use in HNSCC patients.…”
Section: Introductionmentioning
confidence: 97%
“…It has long been understood that EGFR overexpression as determined by immunohistochemistry is associated with poor survival in HNSCC patients. [5][6][7][8] Furthermore, recent comprehensive genomic analyses of HNSCCs have confirmed that EGFR is altered by increased copy number and mutations. [9][10][11] Based on these data, EGFR-targeted agents have been developed and cetuximab, a monoclonal antibody directed against EGFR, is currently FDA-approved for use in HNSCC patients.…”
Section: Introductionmentioning
confidence: 97%
“…Variants of the genes encoding the EGFR family are oncogenes of various tumors. Upregulation of EGFR expression in many human epithelial cancers is associated with advanced tumor stage and an unfavorable prognosis (6,7). Thus, EGFR is considered to be not only a useful prognostic biomarker but also a promising therapeutic target, and specific anti-EGFR monoclonal antibodies (mAbs) to extracellular domains of the proteins, and tyrosine kinase inhibitors (TKIs), have been developed and used in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated the relationship between high EGFR protein expression (as determined by IHC) and poor outcome in HNSCC. Results have been varied, with several groups showing correlations between EGFR protein levels and outcome (11,(16)(17)(18)(19)(20)(21) whereas other groups have shown no correlation (22,23). Increased EGFR gene copy number in HNSCC, as determined by FISH, was reported by Chung and colleagues (24), who showed that high EGFR gene copy number (as defined by high polysomy or amplification) was frequent in HNSCC and was a negative prognostic marker.…”
Section: Introductionmentioning
confidence: 99%